Large lungworms (Nematoda: Dictyocaulidae) recovered from the European bison may represent a new nematode subspecies. (December 2020) - Pyziel, Anna M.; Laskowski, Zdzisław; Dolka, Izabella; Kołodziej-Sobocińska, Marta; Nowakowska, Julita; Klich, Daniel; Bielecki, Wojciech; Żygowska, Marta; Moazzami, Madeleine; Anusz, Krzysztof; Höglund, Johan
Abstract: Although the Dictyocaulus lungworm, the agent of dictyocaulosis, is one of parasitological threats to European bison, its systematic position remains unclear. The aim of the present study was to evaluate the morphological features of the lungworm and the pathological lesions it induces, and to analyse mitochondrial ( mt ) genetic markers for systematic and molecular epidemiological studies. The morphological findings indicate that Dictyocaulus lungworms of European bison can be distinguished from those of cattle on the basis of differences in buccal capsule wall length, total body length, and spicules length in males, all of which were significantly longer in those of European bison. Nucleotide diversity calculated from pairwise sequence alignments of partial cytochrome c oxidase subunit 1 ( cox 1), cytochrome B ( cyt B) and NADH dehydrogenase subunit 5 ( nad 5) of specimens from cattle and European bison varied from 1.7% for nad 5, 2.1% for cyt B, to 3.7% for cox 1 gene. Thus, among the lungworms of European bison and cattle, nad 5 and cyt B were the most conserved proteins, whereas cox 1 was the most diverse. The mt cyt B marker gene may be a suitable candidate for distinguishing between the two genotypes, as nad 5 demonstrated the greatest within-genus sequence variation. The lung tissue of infected European bison manifests signs of verminous pneumonia characterized by interstitial pneumonia, bronchitis and bronchiolitis. Therefore, it appears that European bison and cattle are infected with slightly diverged, morphologically-different, genotypes of D. viviparus, indicating they belong to two separate worm populations. We propose, therefore, that the lungworm of European bison should be classified as D. viviparus subsp. bisontis . Graphical abstract: Image 1 Highlights: European bison harbour a unique morphotype and genotype of Dictyocaulus viviparus . Mt cytB is an efficient genetic marker for studying large lungworms in bovids. European bison lungworm can be classified as D. viviparus subsp. bisontis . Pathologies induced by a newly described nematode subspecies mirrored those of lungworm in cattle.